Single stage boost cascaded multilevel inverter for photovoltaic applications - Sriramalakshmi, P.; Angalaeswari, S.; Sujatha, M. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This article discusses a high-gain five-level SL-SC-based cascaded multilevel qSBI (qSBMLI) for photovoltaic applications. A combination of switched inductor and switched capacitor structure produces a boost at high levels. Two identical SL-SC-based qSBI modules are cascaded and powered with two stiff DC voltage sources of 18 V each. The DC voltage of 18 V obtained from two different DC voltage sources is applied to each module. An 18 V DC voltage is supplied to a single module-A, which produces a DC link voltage (VPN) of about 240 V at the inverter's input side. The modulation index (MI) is selected as 0.68, and the duty ratio is kept at 0.3. The boost factor is obtained as 13.3, and the load voltage of 150 V is achieved across the resistive load. Hence, the voltage gain is 6.9. The proposed topology delivers 337 W of power to the load at an efficiency of 73%. The complete circuit topology and its operations are analyzed in MATLAB/Simulink. The control signals for the power switches are produced using the field programmable gate array (FPGA) SPARTAN 3E Kit. When the proposed circuits are analyzed and compared with the existing classical topologies, the proposed one shows the superior performance.